La conquista di Tripoli nel 1510 vista della Sicilia - Traselli, Carmelo (Mélanges en l'honneur de Fernand Braudel. 1, Histoire économique du monde méditerranéen, 1450-1650, 1973)
Keywords: Famille Samūmnī; Relations – Djerba – Sicile

Aperçus sur l'entrée de l'île de Djerba dans l'orbite ottomane - Veinstein, Gilles (Revue d'Histoire Maghrébine, 1983)
Based on three documents from the Ottoman archives dated 1552, some light is shed on the circumstances in which the Ottoman rule began to implant itself on the island of Jerba, 22 years before Tunis itself was conquered and the Beylerbeylik was installed in 1574
Keywords: Archives – Istanbul; Empire ottoman – Djerba – 16e siècle; Famille Samūmnī; Invasions chrétiennes – Djerba